2022
DOI: 10.3390/v14071543
|View full text |Cite
|
Sign up to set email alerts
|

Hepadnavirus DNA Is Detected in Canine Blood Samples in Hong Kong but Not in Liver Biopsies of Chronic Hepatitis or Hepatocellular Carcinoma

Abstract: Chronic hepatitis and hepatocellular carcinoma (HCC) caused by the hepadnavirus hepatitis B virus (HBV) are significant causes of human mortality. A hepatitis-B-like virus infecting cats, domestic cat hepadnavirus (DCH), was reported in 2018. DCH DNA is hepatotropic and detectable in feline blood or serum (3.2 to 12.3%). Detection of HBV DNA has been reported in sera from 10% of free-roaming dogs in Brazil, whereas 6.3% of sera from dogs in Italy tested positive for DCH DNA by real-time quantitative PCR (qPCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The DCH-derived preS1 peptide bound to NTCP from a wide range of mammals ( Figures 4B and 4C ). Although possible transmission cases of DCH to dogs have been reported (Choi et al, 2022; Diakoudi et al, 2022), the binding of the DCH-derived preS1 peptide to dog NTCP was weak.…”
Section: Resultsmentioning
confidence: 91%
“…The DCH-derived preS1 peptide bound to NTCP from a wide range of mammals ( Figures 4B and 4C ). Although possible transmission cases of DCH to dogs have been reported (Choi et al, 2022; Diakoudi et al, 2022), the binding of the DCH-derived preS1 peptide to dog NTCP was weak.…”
Section: Resultsmentioning
confidence: 91%
“…Our phylogenetic analysis results showed that all positive samples obtained from domestic cats from Türkiye localized into Orthohepadnavirus genus. These findings raise the question of whether DCH can affect other domestic (Capozza, Decaro et al, 2021;Capozza et al, 2023;Choi et al, 2022;Diakoudi et al, 2022) or wild carnivores. We believe that future studies investigating hepadnaviruses in different carnivorous species are needed to understand the origin of DCH and its relationship with other species.…”
Section: Discussionmentioning
confidence: 99%
“…For samples testing DCH-positive by cPCR and/or qPCR, genome sequencing was carried out using overlapping nested PCRs (nPCR) designed here, and a panhepadnavirus nPCR described previously [ 21 , 22 ]. Primers and PCR conditions for the PCRs are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%